2003
DOI: 10.1002/immu.200310014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anti‐macrophage inflammatory protein‐1α on leukocyte trafficking and disease progression in experimental autoimmune uveoretinitis

Abstract: This study has enabled us to identify the influence of the chemokine, macrophage inflammatory protein-1 § (MIP-1 § ), on leukocyte behavior at the blood-retina barrier in vivo and its link with the inflammatory process and disease pathogenesis. MIP-1 § has not previously been thought to be effective under conditions of physiological shear flow. However, short-term anti-MIP-1 § treatment inhibited leukocyte slowing and accumulation and subsequent extravasation of leukocytes at the blood-retina barrier in animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 30 publications
(29 reference statements)
0
16
0
Order By: Relevance
“…3 In vivo monocyte trafficking was studied using our scanning laser ophthalmoscopy (SLO) technique as described. 22,23 This nonsurgical technique minimizes any leukocyte trafficking artifacts. The retinal vasculature is imaged through the intact cornea, and adoptively transferred leukocytes may be tracked as they enter through the retinal artery, traverse the capillary network, and exit through the retinal vein.…”
Section: Methodsmentioning
confidence: 99%
“…3 In vivo monocyte trafficking was studied using our scanning laser ophthalmoscopy (SLO) technique as described. 22,23 This nonsurgical technique minimizes any leukocyte trafficking artifacts. The retinal vasculature is imaged through the intact cornea, and adoptively transferred leukocytes may be tracked as they enter through the retinal artery, traverse the capillary network, and exit through the retinal vein.…”
Section: Methodsmentioning
confidence: 99%
“…MIP-1a mRNA, on the other hand, was not expressed at any of the time points studied. It has, however, been reported that MIP-1a is of major importance in the recruitment of leukocytes into the ocular lesions in EAU [22]. A possible explanation of these conflicting results could be the different type of disease manifestation in the mouse and rat EAU models.…”
Section: Studies On Animalsmentioning
confidence: 87%
“…15 These chemokines can be produced by T cells following T-cell receptor engagement or after nonspecific activation 16 and have been implicated in a range of inflammatory conditions 17,18 including those with an autoimmune basis. 19,20 However, T cells from some normal donors may also produce CCL3 and CCL4 constitutively, and T-cell clones have been established from normal donors that produce substantial levels of CCL3 and CCL4. 21 It is not known whether this spontaneous production is due to inherent genetic factors or whether it has an environmental basis.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that treatment with neutralizing antibody to CCL3 can reduce the severity of experimental autoimmune uveitis, an animal model of PII. 20 Regulation of CCL3 and CCL4 production by T cells infiltrating the retina is important to protect the retina from an inflammatory response, and the RPE cells are likely to be key to this regulation.…”
Section: Resultsmentioning
confidence: 99%